Pengaruh Servant Leadership, Komitmen Organisasi dan Kompetensi terhadap Kinerja Karyawan pada Bank Mitra Bali Mukti Jaya Mandiri di Bangli - Wardani, Ni Komang Indah Belia; Kawiana, I Gede Putu; Suartina, I Wayan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This research was carried out at Bank Mitra Bali Mukti Jaya Mandiri Bangli, which is one of the banks in Bali. Before conducting research, researchers discovered problems related to the decline in the realization of credit targets issued by banks. The phenomenon of the large number of employees leaving and leaving Bank Mitra Bali Mukti Jaya Mandiri Bangli can be related to the employee's organizational commitment. There are still certain things that employees have not been able to fulfill in terms of employee organizational commitment in its implementation. This research used saturated sampling, so the sample from this research was 46 employees of Bank Mitra Bali Mukti Jaya Mandiri Bangli. The analysis technique used is multiple linear regression analysis test. The results of this research are that servant leadership, organizational commitment and competence partially have a positive and significant effect on employee performance at Bank Mitra Bali Mukti Jaya Mandiri Bangli. Simultaneously servant leadership, organizational commitment and competence have a significant influence on employee performance at Bank Mitra Bali Mukti Jaya Mandiri Bangli.